Examining physical training versus physical and mental training programmes in Swimrun semi-professional athletes: A randomised, controlled, trial - Francesco Chirico; Giuseppe Ferrari; Giuseppina Rasà (Journal of Health and Social Sciences)
Objective: The purpose of this study was to identify the effect of two psychological interventions, named ‘Mental imagery’ and ‘Motivational self-talk’ training used in combination, on perceived excertion and flow state in a sample of Swimrun semi-professional athletes. Methods: Thirty male semi-professional athletes, enrolled for a Swimrun competition, were randomly selected into an experimental group (EXP) and a control group (CON). The modified Borg Scale of Perceived Exertion (RPE) and the Flow State Scale (FSS) were the dependent variables. Before a Swimrun competition, the EXP Group performed both physical and mental training programs, while the CON group only performed a physical training program. Immediately after the race, we measured the dependent variables in both groups. Results: The results of unpaired-t test showed that levels of perceived exertion were less in EXP group than CON group, (t(28) = 12.87, P < .001), while levels of flow state were higher in EXP group than CON group (t(28) = 5.96, P < .001), immediately after the end of the endurance competition. The use of both mental imagery and self-talk training in order to reduce perceived exertion and improve flow state was supported (P < .001). Discussion and Conclusion: The findings of this study support the psychobiological model of endurance performance. Our research is the first to demonstrate that mental imagery used in combination with motivational self-talk can reduce the perceived exertion and improve the flow state in Swimrun athletes during their endurance performance.